2011
DOI: 10.1142/s0219633611006529
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Density Functional Theory Study on the Electronic Excited-State Hydrogen Bonding Dynamics of Methyl Acetate in Aqueous Solution

Abstract: The time-dependent density functional theory (TDDFT) method has been carried out to investigate the hydrogen-bonding dynamics of methyl acetate ( CH 3 CO 2 CH 3) in hydrogen-donating water solvent. The ground-state geometry optimizations, electronic transition energies and corresponding oscillation strengths of the low-lying electronically-excited states for the isolated CH 3 CO 2 CH 3 and H2O monomers, the hydrogen-bonded CH3CO2CH3-(H2O)1, 2 complexes have been calculated using DFT and TDDFT methods respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…The calculated metric parameters of hydrogen bonds HB-1 and HB-2 and 1 H NMR chemical shift of H9 and H12 of complex 2 in the S0 and S1 states. 49 Thus, from the three aspects above, we have demonstrated that the hydrogen bond HB-2 was strengthened in the S 1 state, which were consistent with the electronic excitation energies. 26 The IR spectra in the S 1 state of complex 2 was calculated with the TDDFT method using the optimized geometric conformation of the excited state as the initial conformation.…”
Section: The Behavior Of Hydrogen Bonding In the Electronically Excitsupporting
confidence: 81%
See 1 more Smart Citation
“…The calculated metric parameters of hydrogen bonds HB-1 and HB-2 and 1 H NMR chemical shift of H9 and H12 of complex 2 in the S0 and S1 states. 49 Thus, from the three aspects above, we have demonstrated that the hydrogen bond HB-2 was strengthened in the S 1 state, which were consistent with the electronic excitation energies. 26 The IR spectra in the S 1 state of complex 2 was calculated with the TDDFT method using the optimized geometric conformation of the excited state as the initial conformation.…”
Section: The Behavior Of Hydrogen Bonding In the Electronically Excitsupporting
confidence: 81%
“…Both of these characteristic stretching frequencies are therefore red-shied on going from the S 0 state to the S 1 state, which demonstrate that the hydrogen bond is increased in the S 1 state. 49 Thus, from the three aspects above, we have demonstrated that the hydrogen bond HB-2 was strengthened in the S 1 state, which were consistent with the electronic excitation energies. The strengthening of HB-2 in the S 1 state could therefore leads to a decrease in the quantum yield of the S 1 state through deactivation and uorescence, as reported by Zhao et al 26,50 In this case, nonradiative decay process from the S 1 state to the S 0 state would become the main dissipative process of deactivation, 51,52 which would ultimately result in the rate of radiative decay process being decreased.…”
Section: The Behavior Of Hydrogen Bonding In the Electronically Excit...supporting
confidence: 81%
“…Zhao and Han [25] demonstrated for the first time that the hydrogen bond strengthening can change the excitation energy of the complex and can induce an absorption redshift as well as the hydrogen bond weakening can induce an absorption blueshift. According to this relationship, one can monitor the hydrogen bonding dynamics by the changes of the excited energies of the related states [26][27][28]. Using this method, Wang investigated the excited-state hydrogen bonding dynamics of hydrogen-bonded complex formed by methyl cyanide and methanol and got the conclusions that the intermolecular hydrogen bonds C:NÁÁÁH-O are significantly strengthened in both the low-lying singlet and triplet electronically excited states of the hydrogen-bonded MeCN-MeOH dimer and hydrogen-bonded MeCN-2MeOH complex [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…When a solute with a polarizable functional group is dissolved into a protic solvent, the solute and the solvent molecules form an intermolecular hydrogen bond (H-bond) [1][2][3][4][5][6][7][8][9][10][11][12]. Intermolecular hydrogen bonding in solution, as a site-specific solute solvent interaction between hydrogen donor and acceptor molecules [13][14][15][16][17][18][19], has been investigated extensively by a variety of experimental and theoretical methods [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [2,[47][48][49][50][51][52][53][54][55][56][57][58][59][60] have demonstrated that the DFT and TDDFT methods can effectively describe the intramolecular and intermolecular excited states. Moreover, some weak interactions in many molecular systems [61][62][63][64][65][66] have been described by DFT or TDDFT methods with comparable accuracy to the higher level.…”
Section: Introductionmentioning
confidence: 99%